2017
DOI: 10.1002/ange.201701883
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Multisite Interactions between Two Intrinsically Disordered Proteins

Abstract: Protein interactions involving intrinsically disordered proteins (IDPs) comprise a variety of binding modes, from the well‐characterized folding upon binding to dynamic fuzzy complexes. To date, most studies concern the binding of an IDP to a structured protein, while the interaction between two IDPs is poorly understood. In this study, NMR, smFRET, and molecular dynamics (MD) simulation are combined to characterize the interaction between two IDPs, the C‐terminal domain (CTD) of protein 4.1G and the nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…It is noteworthy that the force field applied in this coarse-grained simulation did not distinguish residues with the same charge as pointed out by Ruff et al [87] Finer force fields may be required to dissect differences among residues. Another example is the 4.1G-CTD–NuMA complex reported by Wu et al [88] They confirmed that these IDRs exhibited diverse conformations in bound state by using REMD simulation as well as single-molecule FRET and NMR experiments. The complex formation is driven by a pair of hydrophobic motifs and opposite charges in each IDR.…”
Section: Fuzzy Complexesmentioning
confidence: 66%
See 1 more Smart Citation
“…It is noteworthy that the force field applied in this coarse-grained simulation did not distinguish residues with the same charge as pointed out by Ruff et al [87] Finer force fields may be required to dissect differences among residues. Another example is the 4.1G-CTD–NuMA complex reported by Wu et al [88] They confirmed that these IDRs exhibited diverse conformations in bound state by using REMD simulation as well as single-molecule FRET and NMR experiments. The complex formation is driven by a pair of hydrophobic motifs and opposite charges in each IDR.…”
Section: Fuzzy Complexesmentioning
confidence: 66%
“…A recent trend of MD simulation studies for IDRs is a collaboration with experimental techniques such as CD, FRET, NMR, SAXS, and kinetic experiments. MD simulations provide atomic models explaining experimental results [74,86,88]. The results obtained from MD simulations suggest new experiments (e.g., design of mutants) [79,83].…”
Section: Discussionmentioning
confidence: 99%
“…Although most of the binding events reported to date involve folded domains, interactions between or with intrinsically disordered regions (IDRs, present in more than half of eukaryotic proteins [ 9 , 10 ]) are also important in many biological reactions: An IDR can contact its folded partner by folding upon binding [ 11 , 12 ]; current literature suggests that it is also common for IDRs to bind “fuzzily” to their folded partners without adapting a fixed conformation [ 13 , 14 , 15 ]. There have only been a few reports on how two IDRs from different proteins interact [ 16 , 17 , 18 ]. This gap in our understanding of protein-protein interaction networks can be filled by discovering new interaction modes between IDRs.…”
Section: Introductionmentioning
confidence: 99%
“…Upon binding to their partners, intrinsically disordered proteins span a continuum in the extent of structuredness, from fully folded to partially ordered to fully disordered. The "extreme" fuzzy complexes in the latter case have been characterized when the partners are another disordered protein or a nucleic acid [1][2][3][4][5] . A third class of partners for disordered proteins comprise membranes [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Many disordered proteins are enriched in charged residues 11 , and interactions between opposite charged residues are crucial features of extreme fuzzy complexes between disordered proteins 1,2 . Likewise the interactions between basic residues of proteins and acidic phosphate groups of nucleic acids are crucial for their high-affinity, fuzzy association [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%